Pengaruh Kepemimpinan, Tuntutan Tugas dan Career Plateau terhadap Stress Kerja, Komitmen Organisasi dan OCB Perawat Rumah Sakit Haji Surabaya - Koesmono, H. Teman (Jurnal Widya Manajemen & Akuntansi, 2007)
The purpose of this research is to find out the effect of leadership, job demand and career plateau on work stress, organization commitment and organization citizenship behavior. The object of the research is nurses in Haji Hospital Surabaya. This hospital was chosen as the place of this research because it serves public and it is governed by East Java government. The result of the research can explain that leadership,job demand and career plateau affect work stress, organization commitment and organization citizenship behavior of the nurses in a positive way.